GENERATING ARRAY OF RANDOM ANGLES IN LABVIEW PROGRAMMING ENVIRONMENT - Куц, Ю. В.; Пирог, Т. М. (Science-based technologies, 2009)
The method of generation of random anglers samples has been considered in the article, which is based on the method of reversed function. The offered method has been realized in the environment of LABVIEW. The resulted example of generation of angular s with Mizes distributing confirmed its efficiency.